2020
DOI: 10.1038/s41598-020-76998-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for post-bronchoscopy pneumonia: a case–control study

Abstract: The bronchoscopy, though usually safe, is occasionally associated with complications, such as pneumonia. However, the use of prophylactic antibiotics is not recommended by the guidelines of the British Thoracic Society. Thus far there are few reports of the risk factors for post-bronchoscopy pneumonia; the purpose of this study was to evaluate these risk factors. We retrospectively collected data on patients in whom post-bronchoscopy pneumonia developed from the medical records of 2,265 patients who received 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In a study of 2,265 patients, post-bronchoscopy pneumonia developed more frequently in patients who had a smoking history or received BAL. Moreover, tracheobronchial stenosis was reported as an independent risk factor for post-bronchoscopy pneumonia [ 27 ]. In patients with lung cancer, old age, current smoking status, and central tumor location were independent predictors of post-bronchoscopy pneumonia [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 2,265 patients, post-bronchoscopy pneumonia developed more frequently in patients who had a smoking history or received BAL. Moreover, tracheobronchial stenosis was reported as an independent risk factor for post-bronchoscopy pneumonia [ 27 ]. In patients with lung cancer, old age, current smoking status, and central tumor location were independent predictors of post-bronchoscopy pneumonia [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that A. baumannii and K. pneumoniae readily colonizes the surfaces of medical devices, especially tracheal tubes, by forming biofilms ( Chung, 2016 ; Roy et al., 2022 ). Bringing colonized bacteria into the lesion during the examination and subsequently causing infection ( Sato et al., 2020 ). Therefore, it is essential to enhance operational hygiene and infection control measures for aseptic procedures ( Manandhar et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In case of post-bronchoscopy fever [4,5], use of prophylactic antibiotics is not recommended according to the guidelines of the British Thoracic Society [6]. Moreover, tracheobronchial stenosis was considered an independent risk factor for post-bronchoscopy pneumonia via a multivariate analysis in a case-control study [7]. Inappropriate use of antibiotics may contribute to falsenegative culture results.…”
Section: Discussionmentioning
confidence: 99%